Anapole-Plasmon Strong Coupling Induced Large Rabi Splitting in Dielectric-Metallic Hybrid Nanostructures - Wei Liu; Jinglei Wang; Haimei Luo; Guiqiang Liu (IEEE Photonics Journal)
Manipulation of light-matter interaction is critical in modern physics, especially in the strong coupling regime. Based on the highly localized field enhancement in the near field, we demonstrate that strong coupling can be achieved in the dielectric-metallic hybrid structure consisting of a perforated Si nanoblock filled with a slotted Ag nanodisk (nanoprism) in its center. Large Rabi splitting of 275 (262) meV is achieved due to the generation of new hybrid energy states via the strong anapole-plasmon coupling. Our results pave a feasible way to realize large Rabi splitting and offer an attractive platform to explore strong coupling regime in the light-matter interaction.